Current Role of Surgery in the Management of Oropharyngeal Cancer - Golusiński, Wojciech; Golusińska-Kardach, Ewelina (Frontiers in Oncology, 2019)
In the last few decades, the surgical treatment of oropharyngeal squamous cell carcinoma (OPSCC) has undergone enormous changes. Until the 1990s, open surgery was the primary treatment for OPSCC. However, due to the potentially severe functional morbidity of this approach, open surgery was largely displaced by concurrent chemoradiotherapy (CRT) in the 1990s. At the same time, new, less-invasive surgical approaches such as transoral surgery with monopolar cautery began to emerge, with the potential to reduce functional morbidity and avoid the late-onset toxicity of CRT. More recently, the growing incidence of HPV-positive disease has altered the patient profile of OPSCC, as these patients tend to be younger and have a better long-term prognosis. Consequently, this has further bolstered interest in minimally-invasive techniques to de-intensify treatment to reduce long-term toxicity and treatment-related morbidity. In this context, there has been a renewed interest in the primary surgery, which allows for accurate pathologic staging and thus—potentially—de-intensification of postoperative CRT. The continuous advances in minimally-invasive surgical approaches, including transoral laser microsurgery (TLM) and transoral robotic surgery (TORS), have also altered the surgical landscape. These minimally-invasive approaches offer excellent functional outcomes, without the severe toxicity associated with intensive CRT, thus substantially reducing treatment-related morbidity. In short, given the increasing prevalence of HPV-positive OPSCC, together with the severe long-term sequela of aggressive CRT, surgery appears to be recapturing its previous role as the primary treatment modality for this disease. While a growing body of evidence suggests that TLM and TORS offer oncologic outcomes that are comparable to CRT and open surgery, many questions remain due to the lack of prospective data. In the present review, we explore the emerging range of surgical options and discuss future directions in the treatment of OPSCC, including the most relevant clinical trials currently underway.